Effects of Autophagy Modulators and Dioxin on the Expression of Epidermal Differentiation Proteins on Psoriasis-Like Keratinocytes in vitro and ex vivo - Kim HR; Kim HO; Kim JC; Park CW; Chung BY (Dove Medical Press, 2022)
Hye Ran Kim, Hye One Kim, Jin Cheol Kim, Chun Wook Park, Bo Young Chung Department of Dermatology, Hallym University Kangnam Sacred Heart Hospital, Hallym University College of Medicine, Seoul, 07441, Republic of KoreaCorrespondence: Bo Young Chung, Department of Dermatology, Hallym University Kangnam Sacred Heart Hospital, Hallym University College of Medicine, Seoul, 07441, Republic of Korea, Tel +82-2-829-9092, Fax +82-2-832-3237, Email victoryby777@gmail.comObjective: Psoriasis is a chronic inflammatory skin disorder associated with impairment of epidermal differentiation. Many signaling pathways, including those involved in aryl hydrocarbon receptor (AHR) and autophagy dysfunction, are reportedly associated with the pathogenesis of psoriasis. However, the discrete effects of dioxin via AHR activation or autophagy on the epidermal barrier remain unclear. In the current study, we evaluated the effects of autophagy modulators (chloroquine [CQ] and rapamycin) and the AHR agonist TCDD on the expression of epidermal barrier proteins in psoriasis-like keratinocytes and psoriasis lesional skin tissue culture.Methods: Polycytokine-stimulated human keratinocytes and psoriasis skin biopsies were treated with TCDD, CQ, or rapamycin, and the expression of keratinocyte differentiation-related factors, such as S100A7, S100A8, HRNR, IVL, FLG, and KRT10, was examined by Western blotting or quantitative-polymerase chain reaction.Results: TCDD upregulated S100A7 and S100A8 expression in polycytokine-stimulated HaCaT cells compared to that in unstimulated cells. CQ decreased HRNR, IVL, and KRT10 mRNA levels, while rapamycin increased HRNR, IVL, and KRT10 mRNA levels in HaCaT cells relative to that in unstimulated cells. Co-treatment with CQ reversed TCDD-induced elevation in FLG, HRNR, and IVL mRNA expression. In psoriasis skin tissue, TCDD induced the upregulation of HRNR, IVL, S100A7, and S100A8 compared with that in normal skin. In ex vivo cultures treated with CQ, IVL expression in psoriasis skin tissue was repressed compared to that in normal skin tissue.Conclusion: Our data suggest that autophagy modulation or AHR activation affects processes involved in epidermal differentiation and relates to the pathogenesis of chronic inflammatory skin diseases with skin barrier abnormalities such as psoriasis.Keywords: aryl hydrocarbon receptor, autophagy, keratinocyte differentiation, 2,3,7,8-tetrachlorodibenzo-p-dioxin, chloroquine